HARMONY AMIDST DIVERSITY: ANALYZING THE EFFECTIVENESS OF CHRISTIAN OUTREACH IN GORONTALO CITY'S RELIGIOUS FABRIC - Aprianti, Ni Kadek Elia; Nani, Yacob Noho; Tohopi, Rustam (Public Policy Journal, 2023)
This research aims to know and describe the Effectiveness of Christian Religious Extension Services (Analysis of Religious Harmony for Christians in Gorontalo City), which is studied from 1. Achievement of Goals, 2. Integration, 3. Adaptation. This research method uses the descriptive qualitative method, while the data collection techniques used are interviews, observation, and documentation. The results of this study indicate that in the effectiveness of Christian Religious Extension Services (Analysis of Religious Harmony for Christians in Gorontalo City) in achieving goals, integration, and adaptation. In general, the services of Christian religious instructors have been carried out well but are still not optimal. In the stage of achieving goals, Christian religious instructors still experience obstacles in reaching and providing counseling to Christian communities in Gorontalo City because the number of Christian religious instructors in Gorontalo City is very minimal. At the integration stage, which relates to procedures and socialization, the process of counseling in Gorontalo City has been carried out well. In the adaptation stage for capacity building, the Office of the Ministry of Religious Affairs of Gorontalo Province, especially the Christian Religious Guidance Office, has carried out various kinds of education and training and technical guidance in conducting counseling in Gorontalo City. However, the government needs to pay attention to the extension workers in improving the performance of the extension workers.Â